Identification of Castor Genotypes Resistant to Graymold in Peatland Area based on Resistance Gene Analogs: A Preliminary Study - Wahibah, Ninik Nihayatul; Atria , Martina; Arini, Arini; Yasir, Sidik (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2024)
Graymold is one of devastating fungal disease of castor plants (Ricinus communis L.) caused by Botryotinia ricini. Resistant germplasm is the basic and essential sources to support castor breeding obtaining disease resistant varieties. Objective of this study was to identify castor genotypes resistant to gray mold in peatland agroforestry area in Kepulauan Meranti that naturally infected by graymold fungal pathogen. This is the first report about castor plants cultivated under peat soil. Infected and uninfected castor plants were sampled and analyzed their Resistance Gene Analog (RGA). Results showed that resistant plants expressed diverse phenotype and amplified DNA fragment using RGA primers. The fragments were similar to ABC transporter gene which is one of RGA classes. Additionally, the fragments revealed P-loop NTPase conserved domain. In contrast, all infected plants failed to produced PCR product. The results indicated that uninfected castor plants can be used as source of resistant trait. Their RGA sequences can be analyzed to develop molecular marker for supporting gray mold resistant breeding program.